1994
DOI: 10.1017/s0265051700001996
|View full text |Cite
|
Sign up to set email alerts
|

Music and the National Curriculum in Primary Schools

Abstract: This inquiry focused on the initial implementation of the National Curriculum for music in primary schools. The findings -from 39 schools in different parts of England -indicate that although some teachers are confident about introducing the new curriculum, many perceive problems implementing the programme as presently formulated. In particular there is a reluctance to teach music history and notation to the extent specified and concern is expressed by class teachers over their ability to cope with all the req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Such a study may provide insight into countries in which composition is more central and ideas that may help American educators incorporate composition in their classrooms. For example, a comparison between English, Australian, and American music education systems that examines prescriptive writing and research, and that follows classroom practices through interviews and observation (Lawson, Plummeridge, & Swanwick, 1994), may be particularly valuable.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Such a study may provide insight into countries in which composition is more central and ideas that may help American educators incorporate composition in their classrooms. For example, a comparison between English, Australian, and American music education systems that examines prescriptive writing and research, and that follows classroom practices through interviews and observation (Lawson, Plummeridge, & Swanwick, 1994), may be particularly valuable.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Firstly, the aforementioned discrepancy between curriculum theory and implementation is detected in the field as well (Reimer, 1989;Lawson et al, 1994;Shepherd & Vulliamy, 1994;Hanley & Montgomery, 2002;Economidou Stavrou, 2004). Secondly, there seems to be a lack of knowledge of what students really do in classrooms (Wing, 1992) and also, although data on secondary school children exist, the perceptions of primary school children about the subject of music are under-researched (Mills & O´Neill, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The 1992 implementation of the statutory curricula for music prompted an early study by Lawson, Plummeridge and Swanwick (1994) that focused on primary schools and the issue of teacher resources. It was reported that only a small number of schools (out of a total of 39) had a comprehensive scheme of music education in place for all children.…”
Section: Music Teachers and Music Teachingmentioning
confidence: 99%